Implikasi Teori Humanistik Dan Kecerdasan Ganda Dalam Pengembangan Pembelajaran PAI - Zubdatul Itqon (Jurnal Pendidikan Islam, 2021)
This study aims to describe the implications of the theory of humanistic learning and multiple intelligences to the learning of Islamic Religioaus education. Thisresearch method is to use literature research or literature research that will be analyzed and concluded. Research data obtained froom book and nournal record. The result of thus study in the form of teori understanding humanistic learning and multiple intelligence. Humanistic learning figure is Abraham Maslow as the Implications of Abraham Maslow Theory in Islamic Religious Edication. While the figure of learning multiple intelligence is Howard Gardner. Conclusion humanistic theory aims to humanize humanity as humanly as possible. The learning process is considered effective if student understand themselves and surrounding environment. Students in a series of learning should ty so that sooner or later he can actualize himself as best he can. Whereas the theory of multiple intelligences is understanding intellectual abilities so that their potential can be optimal